Polyvinylpolypyrrolidone-Supported Boron Trifluoride; Highly Efficient Catalyst for the Synthesis of N-tert-Butyl Amides - Masoud Mokhtary; Faranak Najafizadeh (E-Journal of Chemistry)
Highly efficient method for the preparation of N-tert-butyl amides by reaction of nitriles with tert-butyl acetate is described using polyvinylpolypyrrolidone-supported boron trifluoride (PVPP-BF3) at 70°C in good to excellent yields. Selective amidation of benzonitrile in the presence of acetonitrile was also achieved. polyvinylpolypyrrolidone-boron trifluoride complex shows non-corrosive and stable solid catalyst elevated Lewis acid property.